Syngeneic B16F10 Melanoma Causes Cachexia and Impaired Skeletal Muscle Strength and Locomotor Activity in Mice - Voltarelli, Fabrício A.; Frajacomo, Fernando T.; Padilha, Camila de Souza; Testa, Mayra T. J.; Cella, Paola S.; Ribeiro, Diogo F.; de Oliveira, Donizete X.; Veronez, Luciana C.; Bisson, Gabriela S.; Moura, Felipe A.; Deminice, Rafael (Frontiers in Physiology, 2017)
Muscle wasting has been emerging as one of the principal components of cancer cachexia, leading to progressive impairment of work capacity. Despite early stages melanomas rarely promotes weight loss, the appearance of metastatic and/or solid tumor melanoma can leads to cachexia development. Here, we investigated the B16F10 tumor-induced cachexia and its contribution to muscle strength and locomotor-like activity impairment. C57BL/6 mice were subcutaneously injected with 5 x 104 B16F10 melanoma cells or PBS as a Sham negative control. Tumor growth was monitored during a period of 28 days. Compared to Sham mice, tumor group depicts a loss of skeletal muscle, as well as significantly reduced muscle grip strength and epididymal fat mass. This data are in agreement with mild to severe catabolic host response promoted by elevated serum tumor necrosis factor-alpha (TNF-), interleukin-6 (IL-6) and lactate dehydrogenase (LDH) activity. Tumor implantation has also compromised general locomotor activity and decreased exploratory behavior. Likewise, muscle loss and elevated inflammatory interleukin were associated to muscle strength loss and locomotor activity impairment. In conclusion, our data demonstrated that subcutaneous B16F10 melanoma tumor-driven catabolic state in response to a pro-inflammatory environment that is associated with impaired skeletal muscle strength and decreased locomotor activity in tumor-bearing mice.